TELAAH SIKAP BERBAHASA MAHASISWA SEMESTER VI TAHUN 2019 PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Nur Khadijah Razak (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Study of Language Attitudes of Semester VI Students in 2019 Indonesian Language and Literature Education Program, Muhammadiyah University, Makassar. This study aimed to describe the factors that determine language attitudes and attitudes towards Indonesian language in semester VI of 2019 Indonesian Language and Literature Education Program, Muhammadiyah University, Makassar. This type of research is a qualitative descriptive analysis research that describes or qualitatively explains the description of a situation. Data collection techniques include interviews, records, and direct observation. The results of this study indicated that the language attitude of students had shown positive language attitude factors in situations and conditions that were in accordance with the ongoing situation. Also, students of semester VI 2019 attitude towards Indonesian Language in Indonesian Language and Literature Education Program, Muhammadiyah University, Makassar had shown pride, loyalty, and awareness of the existence of language norms.